Stability and Predictive Value of Intellectual Functioning in Neurofibromatosis Type 1 Beginning in the Preschool Years - (:unkn) unknown (My University, 2020)
Neurofibromatosis type 1 (NF1) is a rare genetic disorder that affects multiple aspects of cognitive functioning, including intellectual functioning, attention, and executive functioning. The predictive value of intellectual functioning (IF) in the preschool years for IF in the school- age and early adolescent years has not been examined in youth with NF1. In this study, the reliability and predictive value of preschool IF for school-age IF were examined using both bivariate correlation and more complex linear mixed models. The participants were 55 youth with NF1 from ages 3 to 13 years. Intellectual functioning was measured with the Differential Ability Scales 2nd edition (DAS-II), an individually administered comprehensive measure of IF. Results indicate that both general IF and verbal functioning can be reliably measured in the preschool years in NF1 and that they hold predictive value for school-age functioning in NF1. In the bivariate correlation models, general IF in the early preschool years appeared to be a particularly strong predictor of school-age IF. Linear mixed models appeared to enhance the prediction of verbal functioning, with models including socioeconomic status (SES) and attention-deficit/hyperactivity disorder (ADHD) symptoms as predictors of IF. Nonverbal IF was generally unreliable in the preschool years and had limited predictive value, particularly once confounding variables and extreme cases were removed in the linear mixed model analysis. In addition, based on the linear models, youth appear to increase in general and verbal IF relative to their peers during the preschool years. However, this trend does not appear to continue in the school-age years, and General Conceptual Ability (GCA), Verbal and Nonverbal scores as a group decrease into the school-age years, likely associated with increased conceptual demands in this period of development. Nuanced understanding of the predictive value of IF in the preschool years in NF1 may be helpful in the assessment of early risk predictors and treatment planning.
Keywords: cognitive functioning; Intellectual Functioning; NF1